2017
DOI: 10.3390/su10010023
|View full text |Cite
|
Sign up to set email alerts
|

Ants: Major Functional Elements in Fruit Agro-Ecosystems and Biological Control Agents

Abstract: Ants are a very diverse taxonomic group. They display remarkable social organization that has enabled them to be ubiquitous throughout the world. They make up approximately 10% of the world's animal biomass. Ants provide ecosystem services in agrosystems by playing a major role in plant pollination, soil bioturbation, bioindication, and the regulation of crop-damaging insects. Over recent decades, there have been numerous studies in ant ecology and the focus on tree cropping systems has given added importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 128 publications
0
39
0
Order By: Relevance
“…In general, invasive species including T. melanocephalum heavily impacts their enviroments as competitors on other ants (Holway et al, 2002;Dejean et al, 2010;Falcão et al, 2017). Also, O. smaragdina is aggressive towards other ant species, defining its territory over multiple trees (Hölldobler & Wilson, 1990;Van Mele, 2008;Devarajan, 2016;Diamé et al, 2017). The interspecific interations with territoriality may be one of the factors giving rise to the species segregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, invasive species including T. melanocephalum heavily impacts their enviroments as competitors on other ants (Holway et al, 2002;Dejean et al, 2010;Falcão et al, 2017). Also, O. smaragdina is aggressive towards other ant species, defining its territory over multiple trees (Hölldobler & Wilson, 1990;Van Mele, 2008;Devarajan, 2016;Diamé et al, 2017). The interspecific interations with territoriality may be one of the factors giving rise to the species segregation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, little is known about the communities of arboreal ants dwelling in the plantations of two these fruits. Moreover, in any fruit plantation in Kalimantan, it has been reported that ants monopolize the major part of the biomass in arboreal arthropods (Pfeiffer et al, 2008;Fayle et al, 2013;Diamé et al, 2017). However, Asfiya et al (2015) suggested that intensive agroforestry practices promote the establishment of non-native ant species in the cocoa plantations of southeast Sulawesi.…”
mentioning
confidence: 99%
“…Ants are major predators of small invertebrates, and they provide several ecosystem services in agrosystems, such as plant pollination, soil bioturbation, bioindication, and the regulation of crop-damaging insects. The multiplicity of their roles is linked to the great diversity of their group compared to other animal taxa [79]. Over recent decades, there have been numerous studies in ant ecology related to their interactions with tree cropping systems and different management, in order to better understand the roles played by ants in orchards as functional elements.…”
Section: Antsmentioning
confidence: 99%
“…The immediate root-soil interface is a zone of high porosity, which is very important for several key rhizosphere processes occurring at this scale, including water and nutrient uptake and gaseous diffusion [50]. These effects highlight the importance of ant activity also in agrosystems, in which production sustainability involves the stability of ecological processes linked to soil quality [79]. a) The application of organic amendments to soil promoted high water infiltration rates and ant activity had little effect on these rates b)…”
Section: Antsmentioning
confidence: 99%
“…Exclusion experiments in various agroecosystems indicate that species‐rich ant communities produce positive net effects on yields (Wielgoss et al ., , Gras et al ., ). Although ants are also involved in some disservices (Mody et al ., , Wielgoss et al ., ), they contribute to sustain many ecosystem services (Del Toro et al ., ; Noriega et al ., ; Diamé et al ., ), such as pest control (Offenberg, , Milligan et al ., ), weed control (Baraibar et al ., ), and several soil‐based services (Sanabria et al ., ). Moreover, key ecosystem services (e.g.…”
Section: Introductionmentioning
confidence: 99%